Development of project-based learning e-modules for powertrain system courses: a systematic literature review - Ilham Ilham; Hasan Maksum; Wawan Purwanto; Dony Novaliendry (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This systematic literature review addresses the limited empirical evidence on integrating e-modules and Project-Based Learning (PjBL) in application-intensive engineering courses, particularly Powertrain Systems. Following PRISMA 2020 guidelines, a Scopus search (2015–2025) identified 600 articles, of which 18 high-quality empirical studies were selected through four screening phases. Meta-aggregation of pre–post data indicates substantial learning gains across domains: cognitive (+24.3%, d = 1.42), affective (+22.7%, d = 1.28), and psychomotor (+25.4%, d = 1.51). Effective e-module features include interactive video tutorials, virtual simulations, and industry-based case studies. Team-based PjBL projects lasting 6–8 weeks emerged as the most suitable format for undergraduate settings. Key challenges involve high development workload, infrastructure limitations, and insufficient faculty readiness. Based on synthesized evidence, this review proposes a structured five-module framework for Powertrain Systems that integrates progressive PjBL complexity, simulation-supported learning, authentic industry contexts, and diversified assessment strategies to enhance learning outcomes.